Upaya Pendidikan Kesehatan Untuk Meningkatkan Pengetahuan Ny.P Dengan Hipertensi - Rachmawati, Dewi Aulia, Supratman, Ph.D, WachidahYuniartika, S.Kep.,Ns.,M.Kep (2017)
Hypertension is one of the world's health problems today, pravalansiprovinai cases of hypertension primen in Central Java in 2011 amounted to 1.96% decrease when compared to 2010 of 2.00%. tallest cases of non-communicable diseases in 2011 in the group of heart and blood vessel disease is hypertension, which is about 634 860 cases (72.13). To overcome the above problems either by providing information to patients with hypertension through health education. Patients who had received health education about hypertension treatment is better to have the opportunity to improve compliance in the treatment of hypertension as much as 0.096 times compared with less gain flattening health education in hypertension. With increased knowledge of patients may increase the patient's awareness about the risk of hypertension and its complications. The purpose of this study was to increase the knowledge and reduce headache in patients with hypertension. Preparation of the method of description dengen case study approach that the scientific method is to collect data, analyze the data and draw conclusions. Writers get data from interviews, physical examination, observation of behavioral study the documentation of books and journals. Results from this study is after 4 visits to their home administration of health education, teach relaxation techniques breath in, compress with hot water, teaching progressive relaxation and teach how to make potions with celery, pain was reduced from 5 to 3 and his blood pressure to 140 / 90 mmHg, and the specific goal is after 4 visits to their home families are able to do so and are expected to create a potion and be able to recognize the healty problems of hypertension. Keywords: Hypertension, health education, knowledge, pain